Physiological requirements for iron in women of reproductive age assessed by the stable isotope tracer technique - Lu, Jiaxi; Cai, Jie; Ren, Tongxiang; Wu, Jinghuan; Mao, Deqian; Li, Weidong; Zhang, Yu; Piao, Jianhua; Wang, Jun; Yang, Lichen; Yang, Xiaoguang; Ma, Yuxia (Nutrition & metabolism, 2019)
Background Iron nutrition is important for the health of women of reproductive age, and defining the physiologic requirement for iron can help them accurately plan the iron intake. However, research on the physiologic requirement for iron in women is insufficient worldwide. This study aimed to further improve the methodology and get more precise data for the physiological requirements for iron in women of reproductive age on the basis of our previous study. Method Sixty-one women of reproductive age who had not been pregnant before and during the whole study were included from Hebei province, China in 2015. Each subject participated in a 2-week metabolic trial with consuming 50 mg of the stable isotope 58 Fe, and were then followed for ~ 800 days. The abundance of 58 Fe and the total iron concentration in the circulation were measured using multi-collector inductively-coupled plasma mass spectrometry and atomic absorption spectroscopy. The physiologic requirement for iron in women of reproductive age was then calculated. Results The average iron circulation rate was 80.4%, and the steady period started from about 1 year. The average physiological requirement for iron of 21 subjects obtained by formula calculation was 1.55 mg/d and 23.63 μg.kg − 1 .d − 1 after adjustment for body mass, and that of 33 subjects obtained by linear regression was 1.29 mg/d, 20.98 μg.kg − 1 .d − 1 after adjustment for body mass. The results by two methods showed no significant difference. The EAR and RNI calculated from this results was 11–13 mg/d and 15–18 mg/d, respectively, both of which were slightly lower than the recommended value in Chinese Dietary Reference Intake (2013). Conclusion The physiological requirements for iron in women of reproductive age were in accordance with other studies, while the EAR and RNI calculated from which were slightly lower than Chinese present recommended value. Trial registration ChiCTR, ChiCTR-OCH-14004302 . Registered 14 February 2014, http://www.chictr.org.cn/enindex.aspx